Unveiling the influence of caffeine on topiramate: metabolomic marker analysis using liquid chromatography-mass spectrometry - Bartoszek, Adrian; Paszkowska, Ewa; Kozub-Pędrak, Anna; Sumara, Agata; Fornal, Emilia (Frontiers in Molecular Biosciences, 2025)
BackgroundEpilepsy affects approximately 70 million individuals globally, posing significant neurobiological and psychological challenges. Despite the availability of numerous antiepileptic treatments, one-third of patients remain resistant to therapy, with a limited understanding of caffeine (CAF) interactions with antiepileptic drugs such as topiramate (TPM). Zebrafish (Danio rerio), which share approximately 70% genetic homology with humans, represent a promising model for epilepsy research.AimTo investigate the metabolomic alterations in zebrafish larvae subjected to a pentylenetetrazol (PTZ)-induced seizure model, specifically focusing on the effects of CAF and TPM.MethodsFour days after fertilization, zebrafish larvae were incubated for 18 h with different doses of TPM or a combination of CAF and TPM. Their locomotor activity was subsequently evaluated. Seizures were triggered by adding a PTZ solution to reach a final concentration of 20 mM. The identification of metabolites was carried out using liquid chromatography-tandem mass spectrometry (LC-MS/MS).ResultsOur findings indicated lipid dysregulation, demonstrating increased levels of Lyso-PC, Lyso-PE, and Lyso-PAF in the epileptic larvae. Administration of TPM exacerbated lipid abnormalities, while CAF exhibited a stabilizing effect.ConclusionThe findings highlight the potential of metabolomic approaches in uncovering novel biomarkers, which could enhance the management and development of therapeutic strategies for epilepsy. Moreover, we highlight the complex interactions between CAF and antiepileptic medications. Our findings establish a foundation for further research to understand lipid metabolism and its relevance in epilepsy, potentially guiding future therapeutic strategies.